THE INVESTIGATION OF WORK-LIFE EXPECTATIONS OF CHEMICAL ENGNERER EMPLOYEES IN TERMS OF VARIOUS VARIABLES - Ragıp ADIGÜZEL (Fırat University, 2019)
The aim of this study is to identify the expectations of the employees in the working life of chemical engineers. For this purpose, chemical engineers’ expectations were measured through a questionnaire consisting of 26 questions and SPSS-18 software package were used for the analysis of the given answers to these questions. A total of 69 chemical engineers, including 34 women and 35 men participated in this survey. The process of assessing the responses given by respondents was conducted in two categories. Firstly, respondents were grouped according to the gender, in the second stage they were grouped according to their professional experience (0-5 years, 5-10 years and 10 years and above). While independent sample t-test was used for comparison between the average of male and female groups, one-way ANOVA was performed for comparison of the average between occupational groups. In this study, when the results were evaluated in terms of gender, reviewing topics like the required importance should be given to health and safety at work, projects should be promoted and reaching European standards in the chemical engineer education in our country came to the fore. On the other hand, when the assessment were done based on professional experience, topics related to equipping chemical engineers’ departments according to industrial aspects of present-day conditions, the measures to be taken against vital hazards in the working environment, the necessity of teamwork in solving technical problems, and updating courses like factory organization and business economics to do business management in factory were noteworthy.